Annual Plan 1994-95 Draft Proposals Volume-II Sectoral Programmes Economic Services - Planning Commission (Planning Commission, 1994)
Meghalaya has a population of 17,74.778 (1991-Census) distributed, over an area of approximately 22,500 Square Kms. the gross cropped area is 239 lakh hectares (provisional) while the net cropped area in 2.00 lakh hectares. A target of gross cropped area of 2.45 lakh hectares and net cropped area of 2.00 lakh hectares is proposed. for the year 1994-95 against the anticipated gross cropped area of 24 lakh hectares during 1993-94. The prior objective of the Agriculture Department is to intensify its policies and programmes which will accelerate the growth of feed grains production, increase productivity levels of the crops, especially of food grains, important cash crops and growth in Horticultural Sector in the State.
Planning Department Government of Meghalaya